Direct of Determination of Surface Proteins of Leishmania Parasite by Proteomic Approach - Yalçın, Talat; Akıllı, Ayşe Necla (01. Izmir Institute of Technology, 2023)
Leishmaniasis is a neglected tropical disease caused by the Leishmania parasite, primarily seen in developing and underdeveloped countries. Due to immigration to our country, the effective population of the disease has increased recently. The lesion, which has visceral and cutaneous forms, can be lethal when it acts on internal organs. Surface proteins are the most crucial part of the parasite and host interaction. The parasite attaches to the host cell through surface proteins, enters the cell, multiplies, suppresses the immune system, and allows many other biological functions. It is the most critical research part in vaccine and biomarker discovery. Generally, cell surface biotinylation and cationic colloidal silica beads with which the surface is coated are used to analyze surface proteins. These methods break down the cell and are more open to contaminant proteins from the cytoplasm and nucleus. In addition, since the surface proteins are rich in hydrophobic amino acids, they are difficult to dissolve in polar solvents. The shaving method, uses a faster and minimal experimental workflow to cut only cell surface proteins without lysing the cell, has been tried in four Leishmania species (L.Tropica, L.Infantum, L.Major, L.Donovani). The shaving method aims to digest cell surface proteins by treating the cell surface with a proteolytic enzyme for a short time. Thus, it is expected to contain fewer contaminants and unwanted proteins. As a result of shaving method analysis with the Fusion Orbitrap Mass Spectrometer, the rate of surface protein defined in 4 different species was 9.34% in L.Tropica, 7.55% in L.Major, 7.9% in L.Infantum, 7.52% in L.Donovani. Consistent with the literature and candidates for biomarker ISCL, KMP-11, Leishmanolysin, PSA-2, ABC transporter, and lanosterol 14α demethylase, proteins were identified. Familiar and different proteins were tabulated.

Leşmanyöz, Leishmania parazitinin sebep olduğu, dünyada daha çok gelişmekte olan ve az gelişmiş ülkelerde görülen, ihmal edilmiş tropikal bir hastalıktır. Ülkemize yapılan göçler nedeniyle son zamanlarda hastalığın etki populasyonu artmıştır. Viseral ve kutanöz olarak iki formu bulunan leşmanyöz iç organlarda etki gösterdiğinde öldürücü olabilmektedir. Parazit ile konak etkileşiminde en önemli kısım yüzey proteinleridir. Parazit, konak hücreye yüzey proteinleri aracılığıyla bağlanır, hücre içine girer, çoğalır, immun sistemini baskılar ve daha birçok biyokimyasal fonksiyonun gerçekleşmesine izin verir. Bu nedenle aşı ve biyomarker keşiflerinin en önemli araştırma kısmıdır. Genellikle yüzey proteinlerinin analizinde hücre yüzeyi biyotinleme, yüzeyin kaplandığı katyonik colloidal silika boncukları gibi yöntemler kullanılmaktadır. Bu yöntemler hücreyi parçaladıkları için sitoplazma ve çekirdekten gelen kontaminant proteinlere daha açık olurlar. Ayrıca yüzey proteinleri hidrofobik aminoasitlerce zengin olduğundan polar çözücülerde çözünmesi zor olmaktadır. Bu çalışmada yaygın olarak kullanılan hücre yüzey proteini analiz yöntemleri yerine, dört leishmania türünde (L.Tropica, L.Major, L.Infantum, L.Donovani) hücreyi parçalamadan ilk olarak hücre yüzeyindeki proteinlerini kesmeyi amaçlayan daha hızlı ve minimal deneysel bir iş akışı olan tıraşlama yöntemi denenmiştir. Tıraş yöntemi, hücre yüzeyini kısa bir süre proteolitik bir enzimle işleyerek plazma zarı proteinlerini kesmeyi amaçlar. Böylece daha az kontaminant ve istenmeyen protein (analizlenmesi hedeflenen yüzey proteinleri dışındaki proteinler) içermesi beklenir. Fusion Orbitrap Mass Spectrometer ile analizlenen shaving metodunun sonucunda L.Tropica, L.Infantum, L.Major, L.Donovani den elde edilen örneklerden 4 farklı türde tanımlanan yüzey protein oranı sırasıyla L.Tropicada %9.34, L.Major de %7.55, L. Infantum da %7.9, L.Donovani de % 7.52 dir. Literatür ile uyumlu biyomerker adayı ISCL, KMP-11, leishmanolizin, PSA-2, lipoprotein, ABC transporter, lanosterol 14α demetilaz proteinleri tanımlandı. Ortak ve farklı proteinler tablolaştırıldı.
Leishmania parazit yüzey proteinlerinin proteomik yaklaşımla direk tayini
Thesis (Master)--İzmir Institute of Technology, Bioengineering, Izmir, 2023
Includes bibliographical references (leaves. 78-85)
Text in English; Abstract: Turkish and English
Keywords: Leishmania; Bacterial proteins; Bacterial cell surfaces